2005
DOI: 10.1136/bmj.38555.648623.8f
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the high risk group for cardiovascular disease in the Norwegian HUNT 2 population according to the 2003 European guidelines: modelling study

Abstract: Objective To estimate the high risk group for cardiovascular disease in a well defined Norwegian population according to European guidelines and the systematic coronary risk evaluation system. Design Modelling study. Setting Nord-Tröndelag health study 1995-7 (HUNT 2), Norway. Participants 5548 participants of the Nord-Tröndelag health study 1995-7, aged 40, 50, 55, 60, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
58
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 19 publications
11
58
0
2
Order By: Relevance
“…The gap between observed and guideline-recommended LLD use may reflect the fact that adherence to Framingham-based thresholds for intervention has been problematic in clinical practice. Norwegian population studies have shown that European SCORE-based guidelines classify most adults at high CVD risk with an ''unfavourable'' high cholesterol [2,5,6]. Implementation of these guidelines may lead to a marked increase in pharmacological treatment, especially in men and among the elderly [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gap between observed and guideline-recommended LLD use may reflect the fact that adherence to Framingham-based thresholds for intervention has been problematic in clinical practice. Norwegian population studies have shown that European SCORE-based guidelines classify most adults at high CVD risk with an ''unfavourable'' high cholesterol [2,5,6]. Implementation of these guidelines may lead to a marked increase in pharmacological treatment, especially in men and among the elderly [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, whereas implementation of the guidelines could imply a larger part of the population on cardiovascular preventive therapy in the future [5,6], variation in lipid-lowering drug (LLD) sales across Scandinavia and the rest of Europe may reflect uncertainty about how to manage existing guidelines in clinical practice [7]. The variations in LLD use between countries have been little investigated, but may be explained by differences in national treatment guidelines and drug reimbursement systems, as well as variations in cardiovascular morbidity [8,9].…”
mentioning
confidence: 99%
“…However, it is important to remember that a paramount aim of the systematic coronary risk evaluation project was to encourage the development of national guidelines on prevention of cardiovascular disease, highlighting the importance of evaluating risk scoring systems against epidemiological data from the population to be screened (Getz et al 2005). In Portugal, this evaluation could be especially relevant, as the Portuguese population is affected by the highest mortality rates from cerebrovascular disease of all the countries in the European Union, being an exception in Western Europe-162/100,000 per year among men and 95/100,000 per year among women (Sarti et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless it would be desirable for the estimates to be independently validated against data from a cohort study. Causal CVD risk factors, even in combination, are poor CVD screening tests [23] [24]. To achieve even a 50% detection rate for a 5% false-positive rate, a risk factor must have a relative risk across the top and bottom quintile groups of about 100 [25].…”
Section: Discussionmentioning
confidence: 99%